2020
DOI: 10.5688/ajpe8241
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Active-Learning Strategies for Teaching Social Determinants of Health in Pharmacy

Abstract: The objective of this scoping review is to review current conceptualizations and measurements of active learning education in pharmacy school as it pertains to social determinants of health (SDOH) and to determine the gaps and limitations in available literature. A secondary objective was to assess simulation-based educational methods related to SDOH in pharmacy. Findings. Sixteen articles were eligible for inclusion. Many simulation-based and non-simulation-based teaching strategies are described. The majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…This work highlights the need for global health educators to develop and validate innovative strategies in assessment, particularly in the area of didactic global health education. Similar to these findings, Kiles et al [ 127 ] further highlighted that there were gaps in the literature regarding global health education. While their review focused on teaching strategies rather than assessing educational outcomes, it also recognized the need for further research on teaching strategies and assessments that may be used to assess the complex skills needed in the global health setting including understanding organizational factors, global healthcare system, and SDOH.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This work highlights the need for global health educators to develop and validate innovative strategies in assessment, particularly in the area of didactic global health education. Similar to these findings, Kiles et al [ 127 ] further highlighted that there were gaps in the literature regarding global health education. While their review focused on teaching strategies rather than assessing educational outcomes, it also recognized the need for further research on teaching strategies and assessments that may be used to assess the complex skills needed in the global health setting including understanding organizational factors, global healthcare system, and SDOH.…”
Section: Discussionsupporting
confidence: 60%
“…Health professional education acknowledges the deficits in the current system [ 131 ]. Current assessment tools provide limited focus on the evaluation of the essential knowledge and skills needed by students to address the complex factors that affect the health of populations including the social determinants of health [ 127 ]. Moreover, because heath care professionals are confined by organizational, institutional, and governmental policies and regulations, an assessment of their cultural competency alone does not address the whole picture.…”
Section: Discussionmentioning
confidence: 99%
“…A review of literature in medical, pharmacy, and other health professional programs demonstrated teaching and learning methods used to incorporate and assess SDOH, and educational strategies for increasing cultural competency and reducing health disparities. 3,5,6 Similarly, pharmacy faculty should develop courses with contents and learning outcomes that revolve around historical racial trauma and impacts of racism (structural, institutional, internalized, and individual) on health. 7 Formative assessments including small group discussions, reflections, research concept papers, concept maps, and the requirement that at least one introductory or advanced pharmacy practice experience be completed in an underserved racial/ethnic minority community are strongly recommended.…”
Section: Strategiesmentioning
confidence: 99%
“…7 Formative assessments including small group discussions, reflections, research concept papers, concept maps, and the requirement that at least one introductory or advanced pharmacy practice experience be completed in an underserved racial/ethnic minority community are strongly recommended. 3,5,6 One review article noted the use of students' clinical rotations as immersion experiences to acquire cultural knowledge and facilitate the application of culturally competent care. 6 Faculty should develop corresponding assessment measures and longitudinal assessment plans for such curricular outcomes.…”
Section: Strategiesmentioning
confidence: 99%
See 1 more Smart Citation